COMPARISON OF ANTIBACTERIAL ACTIVITY OF LEAVES EXTRACTS OF TECTONA GRANDIS, MANGIFERA INDICA, AND ANACARDIUM OCCIDENTALE - K., Krishnananda Kamath; Shabaraya, A. Ramakrishna (International Journal of Current Pharmaceutical Research, 2016)
Objective: World Health Organization estimated that 80% of people worldwide rely upon herbal medicines for some aspect of their primary healthcare. For most of the herbs, the specific ingredient that causes therapeutic effect is not known. Bacterial infections are one of the prominent causes of health problems, physical disabilities and mortalities around the world. Plants have been used in medicine as antimicrobial agents since ancient times could provide a promising solution for drug-resistant species. The present study involves comparison of the antibacterial activity of ethanolic extract leaves of Tectona grandis (teak), Mangifera indica (mango), and, Anacardium Occidentale (cashew). Methods: Authentication, morphological studies and phytochemical screening studies on alcoholic extracts of leaves were carried out. Antibacterial activity was carried out by using different concentrations of extracts on bacterial strains of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa by using agar well diffusion method and results were compared. Results: Preliminary phytochemical screening of extracts revealed the presence of alkaloids, glycosides, saponins, resins, tannins and flavonoids. Antibacterial activity was observed in the concentration range of 25-100 mg/ml for all the extracts except T. grandis leaves. They are effective at 50-100 mg/ml concentration. Conclusion: Comparison of results reveals that leaves of T. Grandis have less antibacterial activity compared to M. Indica and A. Occidantale extracts. Keywords: Teak, Mango, Cashew Leaves Extracts, Phytochemical Screening, Antibacterial activity